NURSING VERSUS ABSENTEEISM IN THE LIGHT OF LITERATURE - Silva, Maria Emília Cirqueira; Ribeiro Maciel, Telma; Santos Silva, Yanca; Xavier Carneiro Dias , Tayla; Natiane da Costa Silva, Adriele; Moura de Assis Sampaio, Lorena; Ramalho Galvão, Caroline; Mirelle Carneiro de França, Lyvia; Conceição das Mercês, Magno; Maria Freitas Coelho, Julita; Figuerêdo de Souza, Alexsandro (Health and Society, 2021)
Absenteeism is an important indicator, not only of illness profile, but also of the situation and organization of work and of the motivation and satisfaction of workers. The increasing rate of absenteeism in the world, can generate overload for other employees. Thus, in view of the increase in this pattern of absence from work, the nursing professional at work can contribute to reducing absenteeism, focusing on the quality of life of the worker. In this sense, this research aimed to highlight the importance of the nurse's performance in the face of absenteeism, considering the identification of the factors that trigger this habitual pattern of absence from the work environment that can cause losses, both for the employer and the employee. To this end, the method used was a bibliographic review so that one could reflect on absences at work versus nursing. It was possible to observe that absenteeism has a managerial, complex and costly nature. However, it can be solved with the nurse's work in the workplace.